Comparative book review: On thinking through and researching fashion today. (1st April 2018) - Bide, Bethan
Fashion Studies: Research Methods, Sites and Practices, Heike Jenss (ed.) (2016) London: Bloomsbury, 248 pp., ISBN 9781472583161, Paperback, £21.99 ISBN 9781472583178, 256 pp., Hardback, £85.00 ISBN 9781472583192, EPUB/MOBI e-book, £21.99Thinking Through Fashion: A Guide to Key Theorists, AgnÈs Rocamora and Anneke Smelik (eds) (2016) London: I.B. Tauris, 320 pp, ISBN 9781780767345, Paperback, £16.99 ISBN 9781780767338, Hardback, £69.99